Association of Expanded Prenatal Care Coverage for Immigrant Women With Postpartum Contraception and Short Interpregnancy Interval Births. Issue 2 (February 2022) - Rodriguez, Maria I.; Kaufman, Menolly; Lindner, Stephan; Caughey, Aaron B.; DeFede, Ana Lopez; McConnell, K. John
Abstract : (Abstracted from JAMA Network Open 2021;4:e2118912) In the United States, many immigrant women with low incomes are reliant on Medicaid for obstetric care. However, prenatal and postpartum care is not covered for a large segment of this group who have been in the United States for <5 years.